2019
DOI: 10.5312/wjo.v10.i3.145
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of Legg-Calvé-Perthes disease: A systematic review

Abstract: BACKGROUNDLegg-Calvé-Perthes disease (LCPD) is a clinical condition affecting the femoral head of children during their growth. Its prevalence is set to be between 0.4/100000 to 29.0/100000 children less than 15 years of age with a peak of incidence in children aged from 4 years to 8 years. LCPD aetiology has been widely studied, but it is still poorly understood.AIMTo analyse the available literature to document the up-to-date evidence on LCPD aetiology.METHODSA systematic review of the literature was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 113 publications
(162 reference statements)
0
41
0
4
Order By: Relevance
“…The etiology of LCPD is still debated as the literature available shows major limitations in terms of great heterogeneity and a lack of high-profile studies. In the systematic review done by Pavone et al [2] which include 64 articles, they reported that in the role of environmental risk factors genetic factors, a congenital or acquired predisposition cannot be excluded in disease pathogenesis. One of the most supported theories involved mechanical induced ischemia that evolved into avascular necrosis of the femoral head in sensible patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of LCPD is still debated as the literature available shows major limitations in terms of great heterogeneity and a lack of high-profile studies. In the systematic review done by Pavone et al [2] which include 64 articles, they reported that in the role of environmental risk factors genetic factors, a congenital or acquired predisposition cannot be excluded in disease pathogenesis. One of the most supported theories involved mechanical induced ischemia that evolved into avascular necrosis of the femoral head in sensible patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…genetic mutation [26][27][28][29]. Whole exome sequencing with detailed genome analysis in such children might help to differentiate Perthes disease with localized manifestation of skeletal dysplasia [30].…”
Section: The Effect Of Non-weight Bearingmentioning
confidence: 99%
“…It is underlined in the literature that some disturbances during prenatal life may have an effect on the unborn skeletal system and be the baseline for developing LCPD [1,2]. However, nowadays only one factor which is tobacco has been confirmed as a factor increasing the possibility of LCPD occurrence [3].…”
Section: Risk Factors During Prenatal Lifementioning
confidence: 99%